2021
DOI: 10.3390/ijms22137052
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sphingolipids Contribute to Health via Intestinal Maintenance

Abstract: As sphingolipids are constituents of the cell and vacuole membranes of eukaryotic cells, they are a critical component acquired from our daily diets. In the present review, we highlight the knowledge regarding how dietary sphingolipids affect our health, particularly our intestinal health. Animal- and plant-derived foods contain, respectively, sphingomyelin (SM) and glucosylceramide (GlcCer) as their representative sphingolipids, and the sphingoid base as a specific structure of sphingolipids also differs depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…Many studies have reported that dietary plant lipids exert beneficial effects on health. Although it is well-known that rice bran contains valuable lipophilic components ( e.g. , tocotorienols and γ-oryzanols), , the lipophilic fraction in the daily intake of polished rice as a staple food has also been reported to improve intestinal impairment .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported that dietary plant lipids exert beneficial effects on health. Although it is well-known that rice bran contains valuable lipophilic components ( e.g. , tocotorienols and γ-oryzanols), , the lipophilic fraction in the daily intake of polished rice as a staple food has also been reported to improve intestinal impairment .…”
Section: Discussionmentioning
confidence: 99%
“…1 Dietary phytosterols containing β-sitosterol and β-sitostanol have been reported to stabilize the blood levels of low-density lipoprotein cholesterol in human. 2 Glucosylceramide (GlcCer) is one of the primary sphingolipids in plants, 3 and we consume a certain quantity of plant-origin GlcCer daily (approximately 50 mg). 4 GlcCer is composed of a sphingoid base (SB) with an amide-linked FA (i.e., ceramide, Cer) and glucose.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids have the potential to prevent and alleviate several diseases, including cardiovascular disease, nonalcoholic fatty liver disease, type 2 diabetes mellitus, and colon cancer. , The functions of dietary sphingolipids in the prevention and alleviation of these diseases may be related to their resistance to digestion and absorption in the gastrointestinal tract.…”
Section: Beneficial Effect Of Dietary Sphingolipids In Disease Preven...mentioning
confidence: 99%
“…However, sphingolipids can be de novo synthesized by the condensation reaction between serine and palmitoyl CoA as the initial reaction and there are no symptoms related to their deficiency as nutrients. Recent emerging evidence has implicated dietary sphingolipids in human health. The structures of sphingolipids in foodstuff are diverse. Their structures depend on biological species, such as mammals, plants, and fungi. However, the details of the differences in the physiological activities of food-derived sphingolipids owing to differences in their structures, including their intestinal absorption and metabolic fate, remain to be determined.…”
Section: Introductionmentioning
confidence: 99%